2013
DOI: 10.1017/s0007114513003668
|View full text |Cite
|
Sign up to set email alerts
|

Stearic acids atsn-1, 3 positions of TAG are more efficient at limiting fat deposition than palmitic and oleic acids in C57BL/6 mice

Abstract: In the present study, we investigated the effect of long-acyl chain SFA, namely palmitic acid (16 : 0) and stearic acid (18 : 0), at sn-1, 3 positions of TAG on obesity. Throughout the 15 weeks of the experimental period, C57BL/6 mice were fed diets fortified with cocoa butter, sal stearin (SAL), palm mid fraction (PMF) and high-oleic sunflower oil (HOS). The sn-1, 3 positions were varied by 16 : 0, 18 : 0 and 18 : 1, whilst the sn-2 position was preserved with 18 : 1. The HOS-enriched diet was found to lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Although male rats that were fed the lard-based and corn oil-based high-fat diets consumed the same amount of calories, lard increased the body weight and size of epididymal fat pads more than corn oil did. Thus, different fatty acids can have distinct effects on adipose accumulation, as already shown by others [ 43 ]. Our results further show that lard, but not corn oil, elicited detrimental effects on male reproductive parameters (fewer normal sperm cells and lower daily sperm production).…”
Section: Discussionmentioning
confidence: 52%
“…Although male rats that were fed the lard-based and corn oil-based high-fat diets consumed the same amount of calories, lard increased the body weight and size of epididymal fat pads more than corn oil did. Thus, different fatty acids can have distinct effects on adipose accumulation, as already shown by others [ 43 ]. Our results further show that lard, but not corn oil, elicited detrimental effects on male reproductive parameters (fewer normal sperm cells and lower daily sperm production).…”
Section: Discussionmentioning
confidence: 52%
“…The authors attributed this observation to the higher content of long chain SFA at the sn ‐1, 3 positions of TAG in POo. In a subsequent paper, Gouk et al (2014) also reported that SFA of different chain length at sn ‐1 and ‐3 positions exert profound effects on fat accretion.…”
Section: Effects Of Palm Oil and Its Fractions On Blood Lipids And LImentioning
confidence: 95%
“…In their review of the dietary effects of saturated fats, German and Dillard (2004) also state stearic acid is not thought to increase cholesterol concentrations and also discuss the importance of the TAG positions of the stearic acid groups on the molecule. Further evidence, from studies on mice metabolism, in support of both positional effects and of the role of stearic over palmitic acid in reducing fat deposition is offered by Gouk et al (2013Gouk et al ( , 2014. In the presence of calcium it is then poorly absorbed.…”
Section: Dietary Impact Of Stearic Acidmentioning
confidence: 99%